2005
DOI: 10.1590/s0100-879x2005000200007
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial hyperresponsiveness and analysis of induced sputum cells in Crohn's disease

Abstract: With the aim of investigating the presence of latent inflammatory process in the lungs of patients with Crohn's disease, 15 patients with Crohn's disease were evaluated by spirometry, the methacholine challenge test, induced sputum, and skin tests for inhaled antigens. Serum IgE, erythrocyte sedimentation rate and hematocrit were also determined. The patients were compared with 20 healthy controls by the Mann-Whitney and Fisher exact tests. Their respiratory physical examination was normal. None had a personal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
(29 reference statements)
2
7
0
Order By: Relevance
“…Bartholo et al reported that MPT was found in 27% of patients with Crohn's disease and none of the control subjects. There were also increased lymphocytes in sputum of these patients with Crohn's disease suggesting the presence of an inflammatory response at respiratory tract 22 . Vigorous activation of CD4 cells in the intestinal mucosa of patients with active Crohn's disease was previously reported 23 .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Bartholo et al reported that MPT was found in 27% of patients with Crohn's disease and none of the control subjects. There were also increased lymphocytes in sputum of these patients with Crohn's disease suggesting the presence of an inflammatory response at respiratory tract 22 . Vigorous activation of CD4 cells in the intestinal mucosa of patients with active Crohn's disease was previously reported 23 .…”
Section: Discussionsupporting
confidence: 65%
“…There were also increased lympho-cytes in sputum of these patients with Crohn's disease suggesting the presence of an inflammatory response at respiratory tract. 22 Vigorous activation of CD4 cells in the intestinal mucosa of patients with active Crohn's disease was previously reported. 23 Recent studies have suggested that the common mucosal immune system may be involved in various T-lymphocyte mediated disorders.…”
Section: Discussionmentioning
confidence: 89%
“…Our search found a few works with somewhat similar but inconclusive reports as discussed below. One study showed a high level of sinonasal disease in patients with Crohn's disease [19], but this is most likely due to an alternate basal airway inflammatory process reported in this patient population [20]. Further supporting our theory is the fact that medically controlling the Th1-predominant Crohn's disease results in the expected counterbalance and emergence of the Th2 sinusitis [21].…”
Section: Discussionsupporting
confidence: 53%
“…Multiple studies have identified gastrointestinal disorders such as irritable bowel syndrome (IBS), Crohn's disease, ulcerative colitis, and gastroesophageal reflux (GERD) as risk factors for BHR [White et al, 1991;Louis et al, 1995Louis et al, , 1999Bartholo et al, 2005]. In the case of IBS, White et al [1991] suggested these individuals may have common alterations in smooth muscle function outside the gastrointestinal tract.…”
Section: Gastrointestinal Disordersmentioning
confidence: 99%